L-Cysteine Alleviates Myenteric Neuron Injury Induced by Intestinal Ischemia/Reperfusion via Inhibitin the Macrophage NLRP3-IL-1β Pathway - Gao, Yifei; Zhang, Haojie; Wang, Yujin; Han, Ting; Jin, Jing; Li, Jingxin; Tang, Yan; Liu, Chuanyong (Frontiers in Pharmacology, 2022)
Ischemia-reperfusion injury is a common pathophysiological process in clinic. It causes various injuries, multiple organ dysfunction and even death. There are several possible mechanisms about ischemia-reperfusion injury but the influence on intestinal myenteric neurons and the underlying mechanism are still unclear. C57BL6/J mice were used to establish ischemia-reperfusion model in vivo. Peritoneal macrophages were used for ATP depletion and hypoxia reoxygenation experiment in vitro. L-Cysteine, as the substrate of hydrogen sulfide, is involved in many physiological and pathological processes, including inflammation, metabolism, neuroprotection, vasodilation, etc. In the current study, we confirmed that intestinal ischemia-reperfusion led to the injury of myenteric neurons. From experiments in vitro and in vivo, we demonstrated that L-Cysteine protected myenteric neurons from the injury. AOAA reversed the protective effect of L-Cysteine. And L-Cysteine played a protective role mainly by acting on intestinal macrophages via decreasing expression of NLRP3, cleaved caspase-1 and mature IL-1β. L-Cysteine increased CBS and H2S produced by intestinal macrophages to protect myenteric mature neurons and enteric neural precursor cells from apoptosis. Moreover, the addition of IL-1β neutralizing antibody alleviated the injury of myenteric neurons and enteric neural precursor cells caused by intestinal ischemia-reperfusion. Our study provided a new target for the protection of myenteric neurons in clinical intestinal ischemia-reperfusion injury.